A social change theory for interpretation of the migration flows of the Bangladeshi labor emigration - P. Shаhanaz (Управление)
The special features of the Bangladeshi emigrant work force have been considered. The explanation of the reason under the theoretical framework of social change has been presented, on which the neoclassical theory of migration, and, also the push and pull factors theory, cannot clarify the specific distribution of migrants, which is observed. The neoclassical theory of migration has been analyzed, which supposes, that economic factors should determine the choice of a destination country by a emigrant, and it shows how the theory would predict, that the distribution of emigrants should be correlated to the relative average income of the hosting countries. Therefore, the theory is not respected in the case of the Bangladeshi emigration. The network model of migration, even though it partially fixes this problem, can still not explain the emergence of enclaves of Bangladeshi citizens in hosting countries.The theory of social changes, with some modifications originating from the network approach and the “governmentality” approach, might however explain the distribution of Bangladeshi emigrants abroad, and it has been assumed, that this theoretical development sheds light on the studied problem and its causes. According to this theory, the Bangladeshi emigration is one part of a global process, which creates a global civilization from a number of previously independent societies. A consequence of this theory is that the flows of migrants should more or less follow the waves of development of a globalised society, and, therefore, that it should be possible to measure modifications in the trend of globalisation by measuring the variation in the flows of migrants, or in their distribution across regions.